Exercise in knee osteoarthritis: do treatment outcomes relate to bone marrow lesions? A randomized trial. Issue 18 (28th August 2017) - Beckwée, David; Vaes, Peter; Raeymaeckers, Steven; Shahabpour, Maryam; Scheerlinck, Thierry; Bautmans, Ivan
Abstract: Purpose: Exercise is effective for reducing knee osteoarthritis (OA) pain but effect sizes vary widely. Moreover, not all knee OA patients perceive beneficial effects. Tailoring specific exercises to subgroups of knee OA patients may increase effectivity. Bone marrow lesions (BMLs) have been suggested as a criterion to define such subgroups. This study aimed to investigate whether BMLs' presence/absence is related to treatment outcomes in a group of knee OA patients who exercised for 18 weeks. Methods : Subjects with symptomatic knee OA started a strength or walking exercise program. BMLs' presence at baseline was assessed. Pain was assessed before and after the intervention with the intermittent and constant osteoarthritis pain (ICOAP) questionnaire. Also the global perceived effect (GPE) on the patient's complaints was rated. Results : Thirty-five patients (strength ( N  = 17) and walking ( N  = 18)) were analyzed for BMLs. BMLs were present in 25 (71%) knees. Five (14%) patients dropped out and 19 (54%) improved (GPE ≥5). All dropouts had BMLs, but no difference was seen between dropouts and retainers ( p  > 0.05). Pain scores did not differ between intervention groups ( p  > 0.05) or between patients with BMLs and without BMLs ( p  > 0.05). Conclusions : Pain scores and GPE was not different between knee OA patients with and without baseline BMLs in this sample. Implications for Rehabilitation: Both walking and strengthening exercises are effective means of improving pain in patients with knee osteoarthritis. In a relatively small sample, this study shows that the presence or absence of subchondral bone marrow lesions, as seen on magnetic resonance images, is not related to treatment outcomes.